2013
DOI: 10.1186/1471-2431-13-161
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of intussusception in Singaporean children aged less than 2 years: a hospital-based prospective study

Abstract: BackgroundContinuous surveillance for intussusception (IS) is important for monitoring the safety of second-generation rotavirus vaccines. The present study aimed to assess the incidence of IS in Singaporean children aged < 2 years.MethodsThis was a prospective, hospital-based, multi-center surveillance conducted in seven hospitals - two public hospitals and five private medical centers between May 2002 and June 2010 in Singapore. Diagnosis of IS (definite, probable, possible, suspected) was based on the case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
3
3
0
Order By: Relevance
“…There were significant variations in the clinical features among the children across the regions, which may be due to the interval for presentation or clinical practices followed at the hospitals (Table 2 ). Death was observed in 1.7% cases, which was comparable to reports from India (1.0%) and other countries from Asia (0.25–6.0%), Latin America (1.0–5.0%), but lower than the African countries (2.0–25.0%) [ 17 , 18 , 24 , 28 , 29 , 31 – 33 ]. Level 1 BCCD was met by 89.1% of the cases, similar to other reports from India [ 5 , 7 , 14 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…There were significant variations in the clinical features among the children across the regions, which may be due to the interval for presentation or clinical practices followed at the hospitals (Table 2 ). Death was observed in 1.7% cases, which was comparable to reports from India (1.0%) and other countries from Asia (0.25–6.0%), Latin America (1.0–5.0%), but lower than the African countries (2.0–25.0%) [ 17 , 18 , 24 , 28 , 29 , 31 – 33 ]. Level 1 BCCD was met by 89.1% of the cases, similar to other reports from India [ 5 , 7 , 14 ].…”
Section: Discussionsupporting
confidence: 74%
“…The regional variation in the classical triad appeared to parallel with the interval between illness onset and hospitalization. Ultrasound was the commonest (95.3%) mode of diagnosis, as reported (72.0-100%) from India and other countries [15,18,[28][29][30]. Ileocolic was the most common location, similar to reports (68.0-79.0%) from India and globally [3,7,8,14].…”
Section: Discussionsupporting
confidence: 73%
“…Compared with our 86 cases, a multicenter island-wide prospective study from 2002-2010 identified 93 infants <12 months of age with the same level 1 intussusception criteria. 24 Although selection bias was possible in our study, this was unlikely because there were no significant differences in baseline demographics and characteristics between cases with intussusception with history of rotavirus vaccine vs those without rotavirus vaccination. Furthermore, the use of SCCS allowed us to control for fixed confounding variables such as genetics, socioeconomic status, sex, individual frailty, and severity of underlying disease.…”
Section: Discussionmentioning
confidence: 93%
“…23 Mortality because of intussusception is very low with a 2-year hospital-based prospective study of intussusception in children <2 years reporting only 1 death (0.6%) from septic shock. 24 In this study, we aimed to investigate the association between RV1 and intussusception over the 7 years since the availability of the vaccine in Singapore and perform a risk:benefit analysis to explore the potential impact of a wider RV1 vaccination program.…”
mentioning
confidence: 99%
“…The trend of the incidence rate of IS in children below 12 months of age in our hospital showed a decreasing pattern, from 142 cases to 15 cases per 100000 children during the observation period. This is quite low compared with 47 cases in United States,13 81 cases in Australia,30 28.9 in Singapore,31 19.70–47.83 in Thailand,32 and 38 in Switzerland 33. There is one report from Jeonbuk Province in Korea showing 236 cases per 100000 children below 12 months of age,22 although nationwide data are needed to fully understand and interpret the results of this study.…”
Section: Discussionmentioning
confidence: 69%